Effect of Family Income on Knowledge, Attitude and Practices Regarding Breast Cancer and its Screening Methods Amongst Women of Lahore, Pakistan - Ayesha Rizwan, Zikria Saleem, Saleha Sadeeqa (Journal of Applied Pharmaceutical Science, 2017)
The study aimed to examine the effects of total family income of a household on the knowledge, attitude and practices regarding breast cancer and its screening methods amongst women of Lahore. A cross-sectional survey was conducted on 504 randomly selected women using a self-administered, structured questionnaire. The study suggested a direct relationship between the household income and the knowledge of women. Mean knowledge was 37.8% in the group having an income of PKR60,000 had mean knowledge 44.4%, 62.7% and 66.47% respectively. Attitudes and practices were independent of the income. However, participants with a monthly income of PKR>10,000 had a general trend of better breast self-exam practices. All the groups almost equally realized the importance of performing BSE, although, the overall practice score was low (35.4%). Findings suggested that overall knowledge was relatively weak in all participants, being lowest in the low-income groups.
Keywords: Knowledge, Attitude, Practices, Breast Cancer, Screening.